2019
DOI: 10.1007/s40430-019-1579-0
|View full text |Cite
|
Sign up to set email alerts
|

Structural vibration analysis with random fields using the hierarchical finite element method

Abstract: Element based techniques, like the Finite Element method, are the standard approach in industry for low frequency applications in structural dynamics. However, mesh requirements can significantly increase the computational cost for increasing frequencies. In addition, randomness in system properties starts to play a significant role and its inclusion in the model further increases the computational cost. In this paper, a hierarchical finite element formulation is presented which incorporates spatially random p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The material properties are assumed to follow normal distribution. 29,30,44 For large stochastic dimensions, sampling techniques such as the MCS are the most computationally efficient approaches available due to the curse of dimensionality. However, when a small number of random variables are considered, the use of Monte Carlo simulation (MCS) is computationally expensive due to the requirement of large sample size.…”
Section: Stochastic Analysis Of Flutter Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The material properties are assumed to follow normal distribution. 29,30,44 For large stochastic dimensions, sampling techniques such as the MCS are the most computationally efficient approaches available due to the curse of dimensionality. However, when a small number of random variables are considered, the use of Monte Carlo simulation (MCS) is computationally expensive due to the requirement of large sample size.…”
Section: Stochastic Analysis Of Flutter Characteristicsmentioning
confidence: 99%
“…Fabro et al. 44 presented highly efficient stochastic hierarchical finite element method to investigate the free and forced vibration responses considering non-Gaussian distribution for the modeling of uncertain system properties.…”
Section: Introductionmentioning
confidence: 99%
“…When considering spatially correlated random variability (see Appendix A), the spatial correlation length should be taken into account. It can be shown that the spatial frequency of the random field increases with the increasing order the KL expansion and that each term of the series have a equivalent spatial frequency representation [78,79]. The proposed approximation is equivalent to a mid-point type of random field discretization.…”
Section: Forced Response Of Nearly-periodic Structures With Slowly Va...mentioning
confidence: 99%
“…Equation 1shows the chosen trigonometric function for this study, which can be used for structures with varying geometries, as by Wahrhaftig [21] in comparison with computational analyses using the finite element method (FEM). The FEM, as an analysis technique in a similar context, was used by Alkloub et al [22] in order to analyze the buckling of reinforced concrete columns with a truncated cone shape and square cross section; by Rodrigues et al [23] to evaluate the buckling of reinforced concrete columns, eccentrically loaded, considering nonlinearities inherent to the system, including creep; and by Fabro et al [24], who employed polynomial and trigonometric interpolation functions to optimize the application in real structures with low frequency.…”
Section: Mathematical Modelingmentioning
confidence: 99%